Frankincense in Dhofar: An Ancient Trade at the Centre of 19th Century Tensions - Owtram, Francis (Qatar Digital Library, 2014)
In recognising the importance of the trade, British colonial records cast light on the state of the ancient trade in Frankincense in the Dhofar region at the end of the 19th century, as well as some conflicts that emerged as a result.
Keywords: Dhofar

Une révolution retrouvée : un beau documentaire sur une guérilla avortées dans le sultanat d'Oman en 1974 - Gester, Julien (Libération, 2016)
Keywords: Dhofar